2019
DOI: 10.1186/s12984-019-0561-5
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the optimal tDCS target for motor rehabilitation

Abstract: Background Transcranial direct current stimulation (tDCS) has been investigated over the years due to its short and also long-term effects on cortical excitability and neuroplasticity. Although its mechanisms to improve motor function are not fully understood, this technique has been suggested as an alternative therapeutic method for motor rehabilitation, especially those with motor function deficits. When applied to the primary motor cortex, tDCS has shown to improve motor function in healthy ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 108 publications
1
32
0
Order By: Relevance
“…These effects were verbally mentioned by the three patients in both stimulation conditions, i.e., anodal and sham tDCS. This good tolerability is in accordance with the known excellent safety profile of tDCS ( Brunoni et al, 2012 ; Bikson et al, 2016 ; Woods et al, 2016 ; Antal et al, 2017 ; Jackson et al, 2017a ; Jackson et al, 2017b ), which is also an important factor to consider this method for treatment in post-stroke patients ( Stagg et al, 2012 ; Gomez Palacio Schjetnan et al, 2013 ; O’Shea et al, 2014 ; Fregni et al, 2015 ; Allman et al, 2016 ; Santos Ferreira et al, 2019 ).…”
Section: Discussionsupporting
confidence: 81%
“…These effects were verbally mentioned by the three patients in both stimulation conditions, i.e., anodal and sham tDCS. This good tolerability is in accordance with the known excellent safety profile of tDCS ( Brunoni et al, 2012 ; Bikson et al, 2016 ; Woods et al, 2016 ; Antal et al, 2017 ; Jackson et al, 2017a ; Jackson et al, 2017b ), which is also an important factor to consider this method for treatment in post-stroke patients ( Stagg et al, 2012 ; Gomez Palacio Schjetnan et al, 2013 ; O’Shea et al, 2014 ; Fregni et al, 2015 ; Allman et al, 2016 ; Santos Ferreira et al, 2019 ).…”
Section: Discussionsupporting
confidence: 81%
“…Studies have shown tDCS itself holds great promise to improve functional performance and help in rehabilitative medicine field via the facilitation and modulation of cortical excitability and plasticity (Santos Ferreira et al, 2019). However, large interpersonal variability in the effects of tDCS is observed due to the variance in the protocol of using tDCS, including the electrode position, dose (current intensity and duration), and differences in the brain structure across people (e.g., skull thickness, subcutaneous fat levels, cerebrospinal fluid density, cortical surface topography, age, gender, and genetics) (Wiethoff et al, 2014).…”
Section: Cortical Excitabilitymentioning
confidence: 99%
“…Specific electrode montages have varied across studies aimed at improving motor performance and symptoms to date, but most of them applied the anode over M1 area (34)(35)(36). Some studies conceptualized alternative motor electrode montages, varying electrode dimensions, and the position of the cathode, in order to optimize the stimulation of the lower limb motor cortex (37,38).…”
Section: Introductionmentioning
confidence: 99%